Energy demands and metabolic equivalents (METS) in U-19 basketball refereeing during official games - Nabli, M. A.; Abdelkrim, N. B.; Castagna, C.; Jabri, I.; Batikh, T.; Chamari, K. (Journal of Sports Medicine & Doping Studies, 2017)
The metabolic demands among U-19 basketball players were studied; however, physical and physiological demands of U-19 basketball refereeing during competition are rather scant. The aim of this study was to analyze the energy expenditure (EE) and the exercise intensity of basketball refereeing during official game and determined as Metabolic Equivalent (METs). Sixteen elite level basketball referees were studied during U-19 basketball games (n=8) for time motion analyses (TMA). The EE data were calculated, using specific equations, from the time spent by the referee in each exercise-intensity zone. During game, referees spent a mean EE of 504.4 ± 77.7 kcal. A significant difference was observed between 113.5 ± 18.2 kcal in the 1st quarter (Q1) and 137 ± 27.5 kcal in the Q4 (p=0.007). The averaged EE (~5 kcal/kg.h) corresponded to "moderate energy intensity" (~5 METs) with a large contribution of the aerobic energy pathway. In all, during 88% of game the intensity was equal or lower than 3.8 METs and in 12% it was higher than 9.8 METs which were considered as low to high-intensity thresholds, respectively. The energetic profile studied in this research confirms that basketball refereeing may be regarded as a clearly intermittent-activity mode with a predominantly aerobic metabolism solicitation. Referees officiating in U-19 basketball games should carry out a physical conditioning regime that prepares them for such an effort. (Abstract)